THE EVOLUTION OF CYBER LAW AND ENTERPRISE INFORMATION SECURITY MANAGEMENT - Sibarani, Sinintha Yuliansih (Faculty of Law, Universitas Pekalongan, 2024)
As information technology develops, regulations and policies related to information security also undergo significant changes to adapt to new threats. This research uses the literature study method. The results show the importance of companies integrating information security policies with applicable laws. Companies need to implement various safeguards including multifactor authentication, encryption, and periodic security audits to mitigate risks and protect information assets. The implementation of these measures not only helps ward off cyber threats but also maintains the company's reputation in the eyes of customers and stakeholders. Secondly, security education and training for employees is a vital component in protecting company information. Employees who are trained on cyber threats and the company's security policies are able to be at the forefront. Continuous training and cyberattack simulations can establish a security culture where all employees play an active role in protecting company information. Third, the importance of collaboration with external parties such as law enforcement, security service providers, and the cybersecurity community. Sharing information on threats and best practices helps companies stay alert to new threats and develop more effective mitigation strategies.